CONSUMER ATTITUDES OF MODERN SOCIETY - Galina Petrovna Prokofeva; Aleksandr Alekseevich Prokofev (Sovremennye Issledovaniâ Socialʹnyh Problem, 2020)
Purpose. The article is devoted to consumption as a natural process of economic agents. The relevance of the appeal to consumption is determined by changes in socio-economic relations that form new consumer attitudes in an era of abundance of goods. By now, consumption has become a complexly structured, heterogeneous integral function of society itself. It is assumed that transnational corporations implement consumer allocation strategies aimed to manage the needs of consumers and consumer attitudes. The authors try to identify risks for society derived from further increase of consumption.